2017
DOI: 10.1016/j.ascom.2017.03.005
|View full text |Cite
|
Sign up to set email alerts
|

Accelerating gravitational microlensing simulations using the Xeon Phi coprocessor

Abstract: Recently Graphics Processing Units (GPUs) have been used to speed up very CPU-intensive gravitational microlensing simulations. In this work, we use the Xeon Phi coprocessor to accelerate such simulations and compare its performance on a microlensing code with that of NVIDIA's GPUs. For the selected set of parameters evaluated in our experiment, we find that the speedup by Intel's Knights Corner coprocessor is comparable to that by NVIDIA's Fermi family of GPUs with compute capability 2.0, but less significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Great effort has been expended to deal with this problem in two ways: (i) to perform the computation in parallel and (ii) to reduce the number of lenses (N * ) or light rays (N rays ) involved in the calculations. For the first one, different parallel strategies based on both CPUs (Chen et al 2017) and graphics processing units (GPUs) have been applied to the IRS method, between which GPUs have shown great computational potential (Thompson et al 2010). For the second, Wambsganss (1999) introduced a hierarchical tree method to reorder the lenses by their distance to individual light rays and group distant lenses into larger cells, allowing the N * directly involved in the calculations to be reduced.…”
Section: Introductionmentioning
confidence: 99%
“…Great effort has been expended to deal with this problem in two ways: (i) to perform the computation in parallel and (ii) to reduce the number of lenses (N * ) or light rays (N rays ) involved in the calculations. For the first one, different parallel strategies based on both CPUs (Chen et al 2017) and graphics processing units (GPUs) have been applied to the IRS method, between which GPUs have shown great computational potential (Thompson et al 2010). For the second, Wambsganss (1999) introduced a hierarchical tree method to reorder the lenses by their distance to individual light rays and group distant lenses into larger cells, allowing the N * directly involved in the calculations to be reduced.…”
Section: Introductionmentioning
confidence: 99%
“…(ii) To reduce the number of lenses (N * ) or light rays (N rays ) involved in the calculations. For the first direction, different parallel strategies based on both CPUs Chen et al (2017) and GPUs have been applied on IRS method, among which GPUs have shown great computational potential Thompson et al (2010). For the second direction, Wambsganss (1999) introduced hierarchical tree method to reorganize the lenses by their distance to individual light and group distant lenses into larger cells, allowing N * directly involved in calculations to be reduced.…”
Section: Introductionmentioning
confidence: 99%
“…,[12][13][14][16][17][18]20,21,24,[27][28][29][30][33][34][35][36][37]39,[42][43][44][45][46][47][48]50,52,55,57,59,63,66,84,86,90,92,93,95,99 IntelMKL 2,17,19,31,32,40,93,99 …”
mentioning
confidence: 99%